2020 IEEE 38th International Conference on Computer Design (ICCD) 2020
DOI: 10.1109/iccd50377.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

Driving Scenario Perception-Aware Computing System Design in Autonomous Vehicles

Abstract: Recently, autonomous driving development ignited competition among car makers and technical corporations. Low-level automation cars are already commercially available. But high automated vehicles where the vehicle drives by itself without human monitoring is still at infancy. Such autonomous vehicles (AVs) rely on the computing system in the car to to interpret the environment and make driving decisions. Therefore, computing system design is essential particularly in enhancing the attainment of driving safety.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Moreover, the work may increase based on the scenarios. For example, a recent study showed that higher obstacle density around an AV can intermittently increase the computational demand [15]. As the compute demand created by real-time AV systems can be very high, it is important to quantify the perception requirement for safe operation, provision the fixed resources in the in-vehicle computer to prioritize important tasks, and use the leftover resources for tasks that will further improve safety and comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the work may increase based on the scenarios. For example, a recent study showed that higher obstacle density around an AV can intermittently increase the computational demand [15]. As the compute demand created by real-time AV systems can be very high, it is important to quantify the perception requirement for safe operation, provision the fixed resources in the in-vehicle computer to prioritize important tasks, and use the leftover resources for tasks that will further improve safety and comfort.…”
Section: Introductionmentioning
confidence: 99%
“…However, this work lacks sufficient understanding on how the computation correlates with the driving environment. Zhao et al [29] perform a field study for autonomous vehicles (AV) to gain insights on how the computing systems should be designed. This work looks into the sequential operation of the AV computational kernels from a safety perspective and present a innovative safety criteria for AV.…”
Section: Introductionmentioning
confidence: 99%
“…This work looks into the sequential operation of the AV computational kernels from a safety perspective and present a innovative safety criteria for AV. Both of these works [27,29] are solely concentrated on AV which have different constraints than mobile robots such as an Unmanned Aerial Vehicle (UAV). Finally, Carlone and Karaman [30] consider the visual-inertial navigation problem, and propose anticipation with environmental cues to build a simplified model on robot dynamics and produce a computationally efficient system.…”
Section: Introductionmentioning
confidence: 99%
“…Since navigation is a primitive task, this frees up resources for higher-level cognitive tasks. Related Work: System Design for Robotics: Prior works have explored individual kernel accelerators with statically set knobs [11], [16], made algorithmic improvements ignoring system implications [9], [14], developed runtime control targeting algorithmic specific knobs [15], [17] or individual kernels [7], [12], and demonstrated the importance of system-environment synergy without exploiting them [5], [8]. In this work, we instead take a holistic view of the end-to-end pipeline, study spatial heterogeneity systematically and design a middleware that adapts our compute subsystem online to this heterogeneity by targeting fundamental and inherent physical space characteristics.…”
Section: Introductionmentioning
confidence: 99%